Structure and properties of Ni22Cr10Al1Y coatings deposited by the vacuum plasma spray process - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2016)
In this study, the aim was to deposit layers of the Ni22Cr10Al1Y coating using the vacuum plasma spray process to protect gas turbine engine components from oxidation and high-temperature corrosion. The coating can significantly affect the properties of the substrate because it forms a composite together with the substrate. The type of the coating deposition process and coating heat treatment, together with the substrate, significantly affect its resistance to high temperature creep. Ni22Cr10Al1Y powder was deposited with a vacuum plasma spray system of the Plasma Technik - AG company using the control panel A-2000 and the plasma gun F4. The coating deposited on the substrate of INCONEL X-750 alloy was thermally treated at 1100ºC for 2 hours in a protective atmosphere of argon. The particle morphology was tested by scanning electron microscopy.The microhardness of layers was tested by the HV0.3 method and the bond strength was tensile tested, in accordance with the standard Pratt & Whitney. The microstructure of the deposited coating layers was examined under a light microscope. Coating etching was done by mixing 2.5ml of nitric acid HNO3 with 7.5ml of hydrofluoric acid HF. The microstructure of the etched coating before and after heat treatment, as well as the thickness of the diffusion zone, were analysed under a light microscope, based on which the coating quality was later assessed.